Interlaminar performance of graphene carboxyl modified CFRP composites: Effect of cryogenic conditioning. (2020) - Patnaik, Satyaroop; Gangineni, Pavan Kumar; Panda, Anwesha; Prusty, Rajesh Kumar; Ray, Bankim Chandra
Abstract: Cryogenic applications in various fields are witnessing an increase in the use of carbon fiber reinforced plastics (CFRPs) considering their low density which imparts them high specific strength and stiffness. Interface quality plays a crucial role in determining the mechanical behavior of CFRP composites which can be improved by adding a nanofiller into the composite. Electrophoretic deposition (EPD) is emerging as a reliable technique to introduce nanofillers into CFRP composites via carbon fiber surface modification route. Graphene-based materials are progressively being used as nanofillers due to their promising thermal, electrical and electronic properties along with excellent mechanical strength. In this work varying amounts of GCOOH have been grafted onto carbon fiber surface via EPD by varying the time of deposition. This work is an attempt to investigate the effect of long term and short term conditioning at cryogenic temperatures on the interlaminar behavior of GCOOH modified composites. Amongst short term cryogenic conditioned samples, modified composites have shown better ILSS and an intermediate deposition of 45 min has shown the best interlaminar behavior (12.5% improvement in ILSS over neat composite), whereas after long term cryogenic conditioning increasing deposition has a detrimental effect.